Pengaruh Umur dan Ukuran Perusahaan Pada Pengungkapan Modal Intelektual dan Dampaknya Terhadap Nilai Perusahaan - Suniari, Ida Ayu Melina; Suaryana, I G.N. Agung (E-Jurnal Akuntansi; Vol 21 No 2 (2017), 2017)
Intellectual capital with all knowledge and technology controlled by a company will make the company able to anticipate and face any form of uncertainty that can threaten its existence. These conditions can be beneficial to increase the value of the company. The I ntellectual C apital D isclosure (ICD) by firms is expected to reduce the level of information asymmetry between companies and users of financial statements and can reduce the cost of capital and be able to enhance the company's reputation. Intellectual capital disclosure is a valuable thing that is disclosed in the company's annual report . The disclosure of intellectual capital is related to the age and size of the company. This study aims to determine the effect of age and size of the company on the disclosure of intellectual capital and its impact on corporate value. This research was conducted at financial services company listed in Indonesia Stock Exchange on 2012-2015. The number of samples taken as many as 53 companies, with the method of determining samples is purposive sampling. Data collection was done through non participant observation. Technique of data analysis using two regression technique that is multiple linear regression analysis and simple linear regression analysis. Based on the results of the analysis found that the age and size of the company have a positive effect on intellectual capital disclosure. Intellectual capital disclosure have a positive effect on the firm's value.